Acting with Inscriptions: Expanding Perspectives of Writing, Learning, and Becoming - Kevin R Roozen (Journal of the Assembly for Expanded Perspectives on Learning, 2021)
This article argues for increased attention to people’s engagements with inscriptions and inscriptional practices and the long-term implications they have for the ongoing production of persons, practices, and social worlds across heterogeneous times, places, and activities. Based on a multi-year case study, this analysis examines one microbiology major’s production and use of inscriptions at the intersections of his participation in both disciplinary science and religious worship and traces the long-term consequences those uses have for his becoming as a scientist of faith. If, as Paul Prior asserts, “ literate activity is not located in acts of reading and writing but as cultural forms of life saturated with textuality, that is strongly motivated and mediated by texts,” then we need to take seriously the full range of semiotic textualities and texts implicated in people’s lives and their roles in people’s meaning-making and becoming.
Keywords: Writing; Learning; Becoming; Inscriptions